PEMODELAN MATEMATIKA PENYEBARAN PENYAKIT LEPTOSPIROSIS DENGAN PENGARUH TREATMENT - Ingrit Ridha Rahayu; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2022)
Leptospirosis is a disease passive from bacteria and affect humans and animals.Leptospirosis is transmitted from human to human, from animal to animal, from animal to human. In this study, we will look for a mathematical model of the spread of Leptospirosis with the effect of treatment. The purpose of this modelling is to determine the spread of Leptospirosis with the effect of treatment, to determine the analysis of the mathematical model of the spread of Leptospirosis with the effect of treatment, and to determine the interpretation of mathematical model of the spread of Leptospirosis with the effect of treatment. This research past by determining the variables, parameters, and assumptions which linked to the problem, so that the mathematical model spread of Leptospirosis disease with the effect of treatment. After that mathematical model of the spread of Leptospirosis disease with the effect of treatment will be analyzed and interpreted. Based on analysis result point out that at a fixed point free disease, where the fixed point free disease is stable.